1998
DOI: 10.1080/08035259850158227
|View full text |Cite
|
Sign up to set email alerts
|

Adult height comparison between boys and girls with precocious puberty after long-term gonadotrophin-releasing hormone analogue therapy

Abstract: We examined 22 girls and 11 boys with idiopathic precocious puberty (IPP) treated with a GnRH analogue for a period of about 4 y. The purpose of our study was to evaluate possible differences between the two sexes in bone growth and skeletal maturation during treatment and in the achievement of final height, and also to study the relative contribution of particular hormones--sex steroids, DHEAS, GH and IGF-I--during the pubertal growth spurt. At the beginning of therapy mean chronological age (CA) was 7.61 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
5
16
0
Order By: Relevance
“…Their FH, in fact, was on average 2.8 cm higher with respect to PH1, but 1.8 cm lower than PH2; consequently almost half of the gain in PH during treatment was lost between the time therapy was stopped and the time adult height was reached. A similar trend has been described by other authors (11,(16)(17)(18)(19) and is probably due to the significant increase of DBA:DCA ratio which has been reported to follow therapy cessation (16,19).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Their FH, in fact, was on average 2.8 cm higher with respect to PH1, but 1.8 cm lower than PH2; consequently almost half of the gain in PH during treatment was lost between the time therapy was stopped and the time adult height was reached. A similar trend has been described by other authors (11,(16)(17)(18)(19) and is probably due to the significant increase of DBA:DCA ratio which has been reported to follow therapy cessation (16,19).…”
Section: Discussionsupporting
confidence: 89%
“…The positive change in predicted stature observed in our patients from the start of therapy until the achievement of adult height was similar to the one recorded by other authors (5,16,19,21) in girls treated with s.c. or i.m. GnRH preparations (from 2.4 to 3.5 cm).…”
Section: Discussionsupporting
confidence: 75%
“…The great majority of patients reached an adult height consistent with the TH (13,14,15,17,18,19,20,21,22,23,24,25), a minority of them did not reach the TH (19,26), and a very small portion of patients remained shorter than the predicted height before treatment (13,27). Discordant results were obtained when comparing the efficacy of treatment in females and males.…”
Section: Adult Heightsupporting
confidence: 61%
“…According to a study by Bajpai et al (21), in patients treated with monthly triptorelin depot, mean HG was similar in females and males (mean HG: 6.4G2.4 cm vs 7.6G1.0 cm respectively). In contrast, Galluzzi et al (13) reported a higher HG in boys (7.3G3.8 cm; nZ11) than in girls (3.3G3.0 cm; nZ22), with an achieved adult height SDS higher in the former than in the latter (0.13G0.91 vs K0.62G0.88; P!0.001). In general, HG was highly variable among studies depending on sample characteristics including the progression of pubertal development.…”
Section: Adult Heightmentioning
confidence: 75%
“…Comparisons between the effects of GnRHa treatment in boys and girls are scarce [6], which is also due to the low incidence of CPP in boys. The number of male patients with an organic aetiology for the development of early puberty is relatively high compared to girls, and more often intracerebral pathology can be observed, further limiting the number of boys with idiopathic CPP [6,7].…”
Section: Introductionmentioning
confidence: 99%